1996
DOI: 10.1002/macp.1996.021970122
|View full text |Cite
|
Sign up to set email alerts
|

Linear non‐conjugated dienes from biomass as termonomers in EPDM synthesis, 2. Comparison with 5‐ethylidene‐2‐norbornene termonomer

Abstract: A comparative study of 5-ethylidene-2-norbornene (ENB) or 5,7-dimethylocta-l,6diene (5,7-DMO) as diene termonomer in ethylene-propylene-diene (EPDM) terpolymer synthesis is presented. The reactivities of the cyclic and linear non-conjugated dienes are first compared in homopolymerization in the presence of two conventional Ziegler-Natta catalytic systems: TiCl,, 1/3A1C13, 14MgC1, associated to AIEt,, and VOCl, (or VCI,) associated to AlEt,Cl. ENB polymerization yields a branched poly(ENB) in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…In previous works we have investigated the copolymerization of 5,7-DMO with ethylene [15,16] and its terpolymerisation with ethylene and propylene, [17][18][19] in the presence of various metallocene catalytic systems. High Full Paper: The grafting of phenol groups on ethylene/5,7-dimethylocta-1,6-diene copolymers and on ethylene/propylene/5,7-dimethylocta-1,6-diene terpolymers was performed, using two different modification procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works we have investigated the copolymerization of 5,7-DMO with ethylene [15,16] and its terpolymerisation with ethylene and propylene, [17][18][19] in the presence of various metallocene catalytic systems. High Full Paper: The grafting of phenol groups on ethylene/5,7-dimethylocta-1,6-diene copolymers and on ethylene/propylene/5,7-dimethylocta-1,6-diene terpolymers was performed, using two different modification procedures.…”
Section: Introductionmentioning
confidence: 99%
“…34 Besides, it was already shown that only 18% of the V in the reaction milieu is present as active species. 35 In a previous study, 25 we observed that the Al/V molar ratio incorporated in polymers remains roughly constant (between 6.0 and 7.5) independent of the initial Al/V molar ratio in the solution, which was attributed to the percentage of active V(III) species. Then it seems that the amount of Al/V, which remains in the polymer, corresponds to the metal ratio necessary to generate the active species.…”
Section: Figurementioning
confidence: 77%
“…The linkage is initiated by the interaction of a PDB with cocatalyst to form an active (carbenium-ion terminated) branch (Kresge et al, 1985;ver Strate, 1985;Pehlert et al, 2001). However, direct vinylic coupling of PDBs has also been observed, for example in vinyl norbornene homopolymers using AlEtCl 2 as catalyst (Kennedy and Makowski, 1967;Dolatkhani et al, 1996). Regardless of the number of intervening links in a branch, the crosslink is not complete until the branch reacts with another PDB.…”
Section: Model Developmentmentioning
confidence: 93%
“…The curve relating the two could be reproduced exactly only by assuming that the amount of consumed PDBs was proportional to the square of the diene content. Also, Dolatkhani et al (1996) studied the kinetics of homopolymer diene systems, some of which crosslinked. The crosslinking systems were ENB=VOCl 3 =AlEt 2 Cl and ENB=TiCl 3 =AlCl 3 .…”
Section: Model Developmentmentioning
confidence: 99%